Clean Energy for Development - Wolfowitz, Paul (2016)
Paul Wolfowitz, President of the World Bank, in the development community, the interaction of energy, environment, and poverty have emerged as a central challenge. Lack of consistent electricity in developing countries is a severe obstacle to doing business. It is also affecting school attendance, particularly among girls. Inefficient energy sources can also pose health problems—as many as 1.6 million deaths per year due to indoor smoke. Rich and poor countries alike need to apply energy-efficient technology to cut greenhouse gas emissions. At the G8 summit in Gleneagles, the World Bank Group was asked to take a leadership role in creating a new framework for clean energy and development, including investment and financing. In the first phase we will propose accelerated investments. In the second phase, we aim to generate new knowledge on technology options and the impact on climate change. Wolfowitz summarized the Bank’s ongoing energy spending activities.